Diversity and Distribution of Zooplankton in Pandu Lake, Telangana, India - Solanki, V. R.; Lingampally, Vasudha; Mahesh, L.; Raja, S. Sabita (Research Aspects in Biological Science Vol. 7, 2022)
A study on zooplankton distribution and abundance of Pandu Lake, Bodhan, Telangana, India was conducted during August 2002 to July 2004 to check its trophic status and provide new insights into its ecology. Zooplankton holds a significant place in the trophic structure and is primarily responsible for the transmission of energy in an aquatic ecosystem. In the Pandu lake the pattern of zooplankton abundance was Rotifera > Ostracoda > Copepoda > Diptera> Cladocera. Among all the zooplankton, rotifers exhibited maximum diversity and population density throughout the study period. Results indicated the eutrophic nature of Pandu Lake. The planktons are good indicators of water quality in Pandu lake and their ecological significance is suggesting to control the nutrient load which is a key source to eutrophication process.